[Determination of trisomy 9p by molecular cytogenetic technology] - Ding, X.; Sanoudou, D.; Yang, F.; Chen, H. (Zhonghua Yi Xue Yi Chuan Xue Za ZhiZhonghua Yi Xue Yi Chuan Xue Za ZhiZhonghua Yi Xue Yi Chuan Xue Za Zhi, 1999)
OBJECTIVE: To use molecular cytogenetic techniques for the determination of complex chromosomal aberrations that could not be distinguished by conventional cytogenetic method. METHODS: Chromosome painting, comparative genomic hybridization (CGH) and color banding chromosome analysis (RxFISH) were used to identify a case with chromosome 9 aberration by G-banding. RESULTS: The patient has a karyotype of 46,XX,9p+ by G-banding. Both chromosomes 9 were uniformly painted, including the extra segment on one of the 9p alleles. CGH revealed a duplication of the entire 9p short arm. After analysis with RxFISH the patient's karyotype could be accurately described as 46,XX,dup9p (p11-->p24::p24-->qter). CONCLUSION: The present report shows that some late technological developments in the field of cytogenetics can facilitate the study of the diseases linked to complex chromosomal aberrations and may find significant application in basic and clinical medical studies.
Ding, XSanoudou, DYang, FChen, HchiCase ReportsEnglish AbstractResearch Support, Non-U.S. Gov'tChina1999/12/03 00:00Zhonghua Yi Xue Yi Chuan Xue Za Zhi. 1999 Dec;16(6):383-5.
Keywords: *Chromosomes, Human, Pair 9; *Cytogenetic Analysis; *Trisomy; Child, Preschool; Female; Humans